2015
DOI: 10.18632/oncotarget.5283
|View full text |Cite
|
Sign up to set email alerts
|

HER2 as a novel therapeutic target for cervical cancer

Abstract: Surgery and radiation are the current standard treatments for cervical cancer. However, there is no effective therapy for metastatic or recurrent cases, necessitating the identification of therapeutic targets. In order to create preclinical models for screening potential therapeutic targets, we established 14 patient-derived xenograft (PDX) models of cervical cancers using subrenal implantation methods. Serially passaged PDX tumors retained the histopathologic and genomic features of the original tumors. Among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
60
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 31 publications
2
60
0
Order By: Relevance
“…We demonstrated that our PDXs and PDX cell models closely recapitulated NSCLC patient tumors histopathologically and genomically by molecular biomarkers, copy number variation. Moreover, we had an experience with developing a heterotopic CC PDX model that is implanted in the subrenal capsule space to do preclinical drug efficacy studies [ 20 ]. The RTK/RAS/RAF pathway is frequently mutated in NSCLC and TKIs, which target activated protein tyrosine kinases, have demonstrated excellent therapeutic efficacy in patients with these molecular alterations [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We demonstrated that our PDXs and PDX cell models closely recapitulated NSCLC patient tumors histopathologically and genomically by molecular biomarkers, copy number variation. Moreover, we had an experience with developing a heterotopic CC PDX model that is implanted in the subrenal capsule space to do preclinical drug efficacy studies [ 20 ]. The RTK/RAS/RAF pathway is frequently mutated in NSCLC and TKIs, which target activated protein tyrosine kinases, have demonstrated excellent therapeutic efficacy in patients with these molecular alterations [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting point is the transition of cytoplasmic HER2 expression of the patient tumors to membranous expression of the PDX tumors. Previously, we reported that HER2 expression transitions from nuclear and cytoplasmic to membranous expression with the serial tumor passages in cervical cancer PDXs [ 20 ]. We hypothesize that the cytoplasmic HER2 protein can migrate to the cell membrane under the influence of the unfolded protein response [ 24 ], or that a minor clone that expresses membranous HER2 becomes predominate with PDX serial passages.…”
Section: Discussionmentioning
confidence: 99%
“…However, clinical studies failed to establish a significant benefit [2830], probably owing to the small number of patients studied and the lack of selection of patients with high risks of recurrence. While several biomarkers as prognosis factors for radiotherapy have been studied such as survivin, cIAP1 and Galectin-1 [3, 7, 3135], the role of these molecules in concurrent chemoradiation therapy (CCRT) remains to be validated, because CCRT has been the gold standard treatment for locally advanced cervical cancer since 1999 [36]. Our study in a well-documented series of cervical cancer patients primarily treatment with radiotherapy reveals that higher SKP2 immunostaining is associated with poor DFS ( P < 0.001), especially locoregional recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies will be needed to clarify the correlation between ClC‐3 expression and HER2 expression/trastuzumab resistance in a particular cancer patient. Anti‐HER2 therapies such as trastuzumab are molecular targeting drugs used in the treatment of gastric, colorectal, and cervical cancers . The STAT3 signaling pathway is associated with high expression levels of HER2 in cervical cancer cells, and ClC‐3 is highly expressed in the HER2‐positive gastric cancer cell line NCT‐N87 (not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Anti‐HER2 therapies such as trastuzumab are molecular targeting drugs used in the treatment of gastric, colorectal, and cervical cancers . The STAT3 signaling pathway is associated with high expression levels of HER2 in cervical cancer cells, and ClC‐3 is highly expressed in the HER2‐positive gastric cancer cell line NCT‐N87 (not shown). ClC‐3 Cl − /H + transporter in addition to ANO1 may be novel and effective targets for the treatment of HER2‐positive cancers.…”
Section: Discussionmentioning
confidence: 99%